ARTS MANAGEMENT IN UZBEKISTAN: MAIN DIRECTIONS AND DEVELOPMENT STRATEGIES (Scientific journal of the Fergana State University, 2022)
This article analyses the role of modern art management in our life, development trends, structures that ensure its characteristics and importance. The framework explores the principles, functions and methods of socio-cultural management aimed at operation and development. As a results, the author givesscientificand practical instructions and suggestions on the issues of training art management specialists and creating training manuals in this regard.